Conservação e qualidade das águas dos aquiferos urbanos no Município de Fortaleza – Ceará - Peixoto, Filipe da Silva (2019)
The thesis aimed to investigate a vulnerability, risk and contamination of urban water resources in the city of Fortaleza - CE, contributing to a holistic view of groundwater as part of a system of urban water components. To archive this demand, 5 articles were developed that, despite different objectives, complement each other around the theme: Article 1 "Recharge in urban aquifers: a review of methodologies", conducted a bibliographical study and identified the specific updating mechanisms of urban aquifers and as methodologies most used for the evaluation of recharge in the last 30 years. The article 2 - " Conservation and protection of the groundwater: methodological review of the aquifer mapping for territorial ordering ", carried out survey of the state-of-the-art research of the vulnerabilities aquifer, such as land use and land use instruments in regions rand natural demarcation units such as hydrographic basins and hydrogeological units; Article 3 – “Urban water system (UWS): contributions to water resource management in urban environment", is a conceptual model for the definition of urban waters, seeking to support urban water management in the non-municipality of Fortaleza; Article 4 " Aquifer vulnerability and contamination risk of groundwater in urban environment ", developed a groundwater contamination risk index - IRCAS applied to an urban aquifer; Article 5 " Influence of land use and sanitation issues in water quality of the urban aquifer ", studied a urban hydrographic sub-basin in the city of Fortaleza. This work search identify if there is relation between sanitary aspects, land use on nitrate contamination in a urban aquifer of the Fortaleza city – Brazil. The class to provide a series of subsidies to the management of urban environments, as well as the means of recharging, pollution and contamination of urban environments, subsidize the protection of environments and the planning of the use of the soil, due to a better state of conservation of the groundwater.